2020
DOI: 10.1177/0049475520964399
|View full text |Cite
|
Sign up to set email alerts
|

Filariasis presenting as isolated pleural effusion: A case report and mini review

Abstract: Isolated pleural effusion is a rare manifestation of filariasis that mimics tuberculosis, especially in endemic regions. We describe a case of lymphocytic and exudative pleural effusion showing microfilaria on pleural fluid cytology. A retrospective review of all cases of filarial pleural effusion reported after 2000 was conducted to evaluate the association between filariasis and pleural effusion as well as to screen the features that can help in accurate detection of these patients. The analysis suggested a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The transthoracic echocardiogram showed left ventricular systolic dysfunction (ejection fraction 44%) and moderate pericardial effusion The serologic test for parasites was positive for Toxocara and Sparganum A combination therapy of albendazole (400 mgBID/2 weeks), praziquantel (600 mgTID/1 day), and corticosteroid (60 mgQD/6 days) At Outpatient Clinic follow-ups and observations over the next 2 years there were no abnormal findings, including pericardial effusion or eosinophilia Savu et al [ 14 ] 43/male Romania Hydatidosis caused by the Echinococcus larvae He was a heavy smoker, occasional consumer of ethanol as well as working with livestock as a shepherd Moderate dyspnea, chest pain and weight loss Multiple cystic formations of various sizes and liquid density within the pleural fluid Elevated eosinophil count, Surgery was performed by right lateral thoracotomy and consisted of removal of the hydatid fluid and cysts found in the pleura. IGG-specific ELISA tests(+) Albendazole 15 mg/kg/day for 6 days before surgery, Albendazole treatment for 1 year with 15 mg/kg/day Follow-up showed no signs of recurrence with a normal chest X-ray and an improved lung volume function at one month, 6 months and 1 year Aggarwal et al [ 15 ] 30/male Uttar Pradesh, India Microfilaria/ Filariasis None Low-grade, intermittent fever for two years, right-sided chest pain and weight loss Chest radiography showed a right-sided pleural effusion with normal parenchymal attenuation Fluid cytology showed degenerated lymphocytes along with a few microfilaria, conforming to the morphology of Wuchereria Bancrofti Diethylcarbamazine 300 mg daily in divided doses Chest radiography repeated 6 weeks later showed complete clearance of the effusion Tourne M et al [ 16 ] 39 Paris Cystic echinococcosis, or hydatidosis None Chest pain associated with sweating and chills Thoracic computed tomography shows two large cystic opacities with endocystic flaky images, including one ruptured in the pleura with right pleural effusion Positive hydatidosis serology, and surgery Treatment by albendazole full-recovery …”
Section: Discussionmentioning
confidence: 99%
“…The transthoracic echocardiogram showed left ventricular systolic dysfunction (ejection fraction 44%) and moderate pericardial effusion The serologic test for parasites was positive for Toxocara and Sparganum A combination therapy of albendazole (400 mgBID/2 weeks), praziquantel (600 mgTID/1 day), and corticosteroid (60 mgQD/6 days) At Outpatient Clinic follow-ups and observations over the next 2 years there were no abnormal findings, including pericardial effusion or eosinophilia Savu et al [ 14 ] 43/male Romania Hydatidosis caused by the Echinococcus larvae He was a heavy smoker, occasional consumer of ethanol as well as working with livestock as a shepherd Moderate dyspnea, chest pain and weight loss Multiple cystic formations of various sizes and liquid density within the pleural fluid Elevated eosinophil count, Surgery was performed by right lateral thoracotomy and consisted of removal of the hydatid fluid and cysts found in the pleura. IGG-specific ELISA tests(+) Albendazole 15 mg/kg/day for 6 days before surgery, Albendazole treatment for 1 year with 15 mg/kg/day Follow-up showed no signs of recurrence with a normal chest X-ray and an improved lung volume function at one month, 6 months and 1 year Aggarwal et al [ 15 ] 30/male Uttar Pradesh, India Microfilaria/ Filariasis None Low-grade, intermittent fever for two years, right-sided chest pain and weight loss Chest radiography showed a right-sided pleural effusion with normal parenchymal attenuation Fluid cytology showed degenerated lymphocytes along with a few microfilaria, conforming to the morphology of Wuchereria Bancrofti Diethylcarbamazine 300 mg daily in divided doses Chest radiography repeated 6 weeks later showed complete clearance of the effusion Tourne M et al [ 16 ] 39 Paris Cystic echinococcosis, or hydatidosis None Chest pain associated with sweating and chills Thoracic computed tomography shows two large cystic opacities with endocystic flaky images, including one ruptured in the pleura with right pleural effusion Positive hydatidosis serology, and surgery Treatment by albendazole full-recovery …”
Section: Discussionmentioning
confidence: 99%
“…The escalating effects of climate warming, global movement, improved awareness of the infection contribute to the growing morbidity of diro lariasis in humans, underscoring its increasing relevance in contemporary medicine. 11,12 In this report we present an exceptionally rare case of pleural effusion due to diro lariasis. This case marks the rst instance of human pulmonary diro lariasis reported in Lithuania.…”
mentioning
confidence: 84%
“…Pleural effusion is a rare manifestation of filariasis that may mimic tuberculosis or other causes of effusion. The majority of clients are young to middle age (median) with a mean age of 36 years old, males, and have higher exposure to disease vectors (1).…”
Section: Case Reportmentioning
confidence: 99%
“…Filariasis is often difficult to diagnose, especially in non-endemic areas. A retrospective search of the PubMed database revealed that only 19 cases were reported between 2000 to 2021 (1). Filariasis is a vectorborne tropical disease that attacks the lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation